2018
DOI: 10.3389/fenvs.2018.00143
|View full text |Cite
|
Sign up to set email alerts
|

Dye Tracer Visualization of Infiltration Patterns in Soils on Relict Charcoal Hearths

Abstract: Anthropogenically modified soils are often characterized by a high heterogeneity of substrates and show unique patterns of water infiltration. Such effects are not limited to intensively used or disturbed agricultural and technogenic soils, but can also occur as legacies of former land use in forested areas. The remains of historic charcoal hearths represent a widespread legacy of historic land use. Soils at relict charcoal hearths (RCHs) are most prominently altered by the deposition of a layer of charcoal-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In Brandenburg, the RCHs are concentrated in areas with slopes <0.5° but they are only slightly overrepresented at slopes between 0.5 and 1°. This finding suggests that colliers preferred flat positions over positions on very slightly inclined surfaces, which might be related to the observation that wood for the hearths was commonly stacked directly on top of the undisturbed soil surface, as shown by stratigraphic analyses of RCH soils in the Tauersche Forst (Hirsch et al, , Schneider, Hirsch, Raab, & Raab, ). In the Northern Bavaria study area, the RCHs are similarly concentrated in flat areas and very slightly inclined surfaces but the distribution of mapped RCHs over slope classes suggests a lower differentiation in site preferences related to slope in the higher‐relief landscape than in the Brandenburg study area.…”
Section: Discussionmentioning
confidence: 82%
“…In Brandenburg, the RCHs are concentrated in areas with slopes <0.5° but they are only slightly overrepresented at slopes between 0.5 and 1°. This finding suggests that colliers preferred flat positions over positions on very slightly inclined surfaces, which might be related to the observation that wood for the hearths was commonly stacked directly on top of the undisturbed soil surface, as shown by stratigraphic analyses of RCH soils in the Tauersche Forst (Hirsch et al, , Schneider, Hirsch, Raab, & Raab, ). In the Northern Bavaria study area, the RCHs are similarly concentrated in flat areas and very slightly inclined surfaces but the distribution of mapped RCHs over slope classes suggests a lower differentiation in site preferences related to slope in the higher‐relief landscape than in the Brandenburg study area.…”
Section: Discussionmentioning
confidence: 82%
“…Still, it is possible that a not balanced elements stoichiometry in RCHs soil could lead to nutrient deficiency in plants, because of positive or negative interaction between nutrients (Marschner, 1995), although European beech foliar chemical composition does not seem to support such a hypothesis. Finally, Schneider et al (2018), found that charcoal hearths soil in an eastern German forest is affected by a high preferential infiltration of water, which imply that large parts of soil remain dry during and after a dry period, thus worsening conditions for plant growth.…”
Section: Dendrometric and Dendrochronological Analysismentioning
confidence: 99%
“…5). There are also more other environmental effects especially on soil physical and chemical properties which was proved by Schneider et al (2018Schneider et al ( , 2019 and Hirsch et al (2018). These issues should be also examined in the future, for the Mała Panew River basin.…”
Section: Other Environmental Effects Of Charcoal Burningmentioning
confidence: 96%